Schooling and Occupational Outcomes in Adults with ADHD: Predictors of Success and Support Strategies for Effective Learning - Simone Varrasi; Francesco Maria Boccaccio; Claudia Savia Guerrera; Giuseppe Alessio Platania; Concetta Pirrone; Sabrina Castellano (MDPI AG, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurobehavioral disorder that is usually diagnosed in childhood. It is characterized by attention deficits, hyperactivity, and impulsivity leading to significant impairment in academic, occupational, familiar, and social functioning. Most of the literature has been focusing on the impact of this condition on infancy and preadolescence, but little is known on its consequences in adulthood. This narrative review addresses this gap by focusing on the studies regarding the schooling outcomes of this population. After identifying the specific clinical and neuropsychological profile of ADHD in adults, this study analyzes their precise needs for effective learning and presents evidence on their academic and occupational achievements. Pharmacological, educational, and rehabilitative factors predicting a positive scholastic and career success are critically reviewed. Finally, this study focuses on the strategies that can improve the learning processes in adults with ADHD by expanding the analysis on executive functions, metacognition, and emotional dysregulation. Schooling outcomes in adults with ADHD, therefore, are conceptualized as a complex measure depending on several variables, like early pharmacological treatment, educational support, neuropsychological intervention, and targeted strategies for life-long learning.